Compression performance and failure mechanism of honeycomb structures fabricated with reinforced wood. (February 2023) - Fan, Zixuan; Ye, Gaoyuan; Li, Shuai; Bai, Zhongyang; Yong, Qiwen; Zhang, Yuhui; Hu, Yingcheng
Abstract: In this paper, a fast-growing poplar wood was selected as the structural raw material to construct a green, eco-friendly, and high-quality building structure. The pretreatment and hot-pressing process were designed to reinforce the poplar wood, and the reinforced poplar square honeycomb structure was further manufactured by the inlay-locking process. Quasi-static axial compression tests were conducted on the reinforced poplar and natural wood honeycomb structures. The results reveal the compression damage mode of the square honeycomb structure to be the shear damage of the honeycomb ribs due to the flexion of the core. The reduced height and increased relative density of the honeycomb structure were able to enhance the strength and elastic modulus. The specific energy absorption of the square honeycomb structures was found to be similar or better than that of other lattice structures. The results reveal that an excellent specific strength and energy absorption can be achieved through poplar reinforced designation, showing great potential for biomass material applications in construction.